Respuesta :

Prove the given

  • (cot A - tan A)cos A = cosec A - 2sinA

Use identities

  1. sin²A + cos²A = 1
  2. cotA = cosA/sinA
  3. tanA = cosA/sinA
  4. cosecA = 1/sinA

Solution

Simplify the LHS by using the identities above to get the RHS:

  • (cot A - tan A)cosA =
  • (cosA/sinA - cosA/sinA)cosA =                         Identities 2 and 3
  • (cosA/sinA)cosA - (cosA/sinA)cosA =               Distribute
  • cos²A/sinA - sinA =                                            Simplify/cancel
  • (1 - sin²A)/sinA - sinA =                                       Identity 1
  • 1/sinA - sin²A/sinA - sinA =                                Distribute
  • 1/sinA - sinA - sinA =                                          Simplify/cancel
  • 1/sinA - 2sinA =
  • cosecA - 2sinA                                                   Identity 4    

Proved